Status Gizi, Aktivitas Fisik dan Asupan Serat Berhubungan dengan Kadar Gula Darah Puasa Penderita DM Tipe 2 - Mia Audina; Tonny Cortis Maigoda; Tetes Wahyu W (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
The purpose of this study was to determine the relationship among nutritional status, activity physical and intake fiber with levels sugar blood fasting on type 2 DM patients in Puskesmas Pasar Ikan of Bengkulu city. Cross-sectional design is used in this research . The subject in research is 33 respondents who have diagnosed DM type 2 by health providers that fulfills criteria inclusion. Collecting data was done by using anthropometrical measurements, interviews structured with PAL, SQ-FFQ. Blood sample was taken by using electro based biosensor system and Easy Touch tool. The statistic analysis was done by Correlation test. This research showed that there was no relationship between blood glucose level in fasting with nutritional status (p = 0.748) . There was a relationship activity physical with GDP (p = 0.029) with negative patterned r = -0.379. There was relationship between fiber intake with GDP (p = 0.039) with negative patterned r = -0.362. There was a significant relationship between physical activity, fiber intake with the fasting blood sugar levels on patients with DM type 2